2022
DOI: 10.1371/journal.pone.0274630
|View full text |Cite
|
Sign up to set email alerts
|

The global polarisation of remote work

Abstract: The Covid-19 pandemic has led to the rise of digitally enabled remote work with consequences for the global division of labour. Remote work could connect labour markets, but it might also increase spatial polarisation. However, our understanding of the geographies of remote work is limited. Specifically, in how far could remote work connect employers and workers in different countries? Does it bring jobs to rural areas because of lower living costs, or does it concentrate in large cities? And how do skill requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…It is argued that accurately determining the skills in human capital data is the first step in resolving this socioeconomic problem [ 145 ]. In the study conducted by Braesemann et al [ 18 ], it was revealed that remote working skills are not evenly distributed around the world, there is a polarization, and southern countries lag behind northern countries and rural areas lag behind cities. In addition, it has been found that employees who do not have sufficient skills in remote work receive less salary than employees who have these skills and are not in equal competitive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that accurately determining the skills in human capital data is the first step in resolving this socioeconomic problem [ 145 ]. In the study conducted by Braesemann et al [ 18 ], it was revealed that remote working skills are not evenly distributed around the world, there is a polarization, and southern countries lag behind northern countries and rural areas lag behind cities. In addition, it has been found that employees who do not have sufficient skills in remote work receive less salary than employees who have these skills and are not in equal competitive conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The managerial literature (Wren and Hay, 1977; Thompson Heames and Breland, 2010; Dagher et al , 2015; Günsel and Yamen, 2020; Braesemann et al , 2022; Cameron et al , 2023; Noponen et al , 2023) agrees that Tayloristic principles have crossed the history of managerial thought. One of Taylor’s main intuitions was to define the production system as a whole made up of men, tools and machinery to be shaped scientifically with the aim of improving its efficiency and productivity (Taylor, 1911).…”
Section: Theoretical Backgroundmentioning
confidence: 97%
“…According to Altenried (2020), instead of producing a "digital mass worker," these labour platforms create a heterogeneous global workforce. Braesemann et al (2022) observe similarities in the spatial division of work between this trend and the offshoring of business process that started in the 1980s; in this case, how increasingly standardized and modularized knowledge work tasks enable the global division of knowledge work between the global north and global south. According to Braesemann et al ( 2022) digitally enabled remote work is likely to reinforce the prevalent global dynamics rather than distributing knowledge work more evenly.…”
Section: Digital Taylorism -Are Algorithms Taking Management Back a H...mentioning
confidence: 99%